A Tripeptide Approach to the Solid‐Phase Synthesis of Peptide Thioacids and N‐Glycopeptides. Issue 69 (7th November 2019) - Schöwe, Markus Julian; Keiper, Odin; Unverzagt, Carlo; Wittmann, Valentin
Abstract: A general and robust method for the incorporation of aspartates with a thioacid side chain into peptides has been developed. Pseudoproline tripeptides served as building blocks for the efficient fluorenylmethyloxycarbonyl (Fmoc) solid‐phase synthesis of thioacid‐containing peptides. These peptides were readily converted to complex N‐glycopeptides by using a fast and chemoselective one‐pot deprotection/ligation procedure. Furthermore, a novel side reaction that can lead to site‐selective peptide cleavage using thioacids (CUT) was discovered and studied in detail. Abstract : Pseudoproline tripeptides are suitable building blocks for the challenging fluorenylmethyloxycarbonyl (Fmoc) solid‐phase synthesis of peptides with an aspartic side‐chain thioacid. These peptides can be chemoselectively ligated with glycosyl amines to form N‐glycopeptides. Alternatively, the aspartyl thioacids are prone to a highly efficient and site‐selective peptide cleavage (peptide CUT, see scheme).